2010
DOI: 10.1007/s10646-010-0555-3
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid-disrupting effects of long-term perfluorononanoate exposure on zebrafish (Danio rerio)

Abstract: Concentrations of perfluorononanoate (PFNA) suggest an obvious increase in the environment, wildlife, and humans. However, the potential toxicity of PFNA still remains to be fully elucidated. Our present work is directed toward evaluating specific thyroid endpoints, and studying the long-term and the trans-generational effects of PFNA on zebrafish. Zebrafish (Danio rerio) were exposed to different concentrations of PFNA (0, 0.05, 0.1, 0.5, and 1 mg/l) from their early life stages (F(0), 23 day post-fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 38 publications
(38 reference statements)
1
40
1
Order By: Relevance
“…Depression of serum total T 4 , free T 4 , and total T 3 has been reported by several authors in PFOS-exposed rats (5)(6)(7)(8), without the concomitant increase in TSH that would be expected through feedback stimulation, whereas PFOA reduced total T 4 and total T 3 in monkeys (9). In contrast, although there has been no report of perfluorononanoic acid (PFNA) exposure and thyroid hormones in mammals, a recent study demonstrated significantly elevated plasma total T 3 in zebrafish after long-term PFNA exposure (10). Reduced responsiveness of the hypothalamic-pituitary-thyroid axis and displacement of circulating thyroid hormones from their plasma protein binding sites were suggested as potential mechanisms of perfluorodecanoic acid (11).…”
mentioning
confidence: 94%
“…Depression of serum total T 4 , free T 4 , and total T 3 has been reported by several authors in PFOS-exposed rats (5)(6)(7)(8), without the concomitant increase in TSH that would be expected through feedback stimulation, whereas PFOA reduced total T 4 and total T 3 in monkeys (9). In contrast, although there has been no report of perfluorononanoic acid (PFNA) exposure and thyroid hormones in mammals, a recent study demonstrated significantly elevated plasma total T 3 in zebrafish after long-term PFNA exposure (10). Reduced responsiveness of the hypothalamic-pituitary-thyroid axis and displacement of circulating thyroid hormones from their plasma protein binding sites were suggested as potential mechanisms of perfluorodecanoic acid (11).…”
mentioning
confidence: 94%
“…Fang et al [37][38][39] described the hepatotoxicity of PFNA in rat; while Zhang et al [40,41] further elaborated the transcriptional and proteomic changes in zebrafish liver after chronic exposure to PFNA. Liu et al [42] reported the thyroid-disrupting effects of PFNA in zebrafish. Immunotoxic effects of PFNA in rats and mice have been shown by Fang et al [43,44] and Rockwell et al [45].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal experiments have shown that PFCs impaired thyroid function (Chang et al 2008;Liu et al 2011). For example, depression of serum THs levels has been reported in PFOS-exposed rats and monkeys (Lau et al 2004).…”
Section: Introductionmentioning
confidence: 99%